Two-layer collaborative optimization for a renewable energy system combining electricity storage, hydrogen storage, and heat storage. (15th November 2022) - Fan, Guangyao; Liu, Zhijian; Liu, Xuan; Shi, Yaxin; Wu, Di; Guo, Jiacheng; Zhang, Shicong; Yang, Xinyan; Zhang, Yulong
Abstract: Renewable energy systems combining hybrid energy storage (HES-RESs) and new energy vehicles are beneficial for realizing net-zero carbon emissions of the building and transport sectors. However, the configuration and operation of HES-RESs lack mature optimization methods, and the competition between systems that consider electric vehicles and hydrogen vehicles is unclear. Therefore, a RES that combines electricity storage, hydrogen storage, and heat storage is proposed. The nonlinear model of the HES-RES is established. A two-layer collaborative optimization model of system design and operation is constructed. The economy, environment, and independence of the HES-RES are improved. Then, the system is applied to a diversified nearly zero-energy community, and the optimization results considering electric vehicles and hydrogen vehicles are compared. The variation in performance, configuration, and operation of the HES-RES are quantitatively analysed with different proportions of hydrogen vehicles. The results show that the annual carbon emissions and costs of the HES-RES considering electric vehicles are reduced by 39.5% and 25.6%, respectively, and the grid interaction is increased by 10.0%, compared to the system only considering hydrogen vehicles. The HES-RES and the optimization results have a positive guiding role for the carbon emission reduction and integration development of the building and transport sectors. Highlights: A system combining electricity storage, hydrogen storage, heat storage is proposed. Two-layer collaborative optimization model of system design and operation is set up. The systems considering electric vehicles and hydrogen vehicles are compared. The stability of the two-layer collaborative optimization method is verified.